2019
DOI: 10.3390/ijerph16142613
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Relationship among Antecedents and Job Satisfaction in Taiwan and Mainland China: Employability as Mediator

Abstract: Previous studies of the relationship between job security and job satisfaction were mostly conducted on research samples in Asia from the perspective of oriental culture; however, under the same cultural background, different social systems might lead to different cognition outcomes. Therefore, this study examines the job security and organizational support of Taiwan and mainland China employees from the perspectives of competence enhancement motivation, and investigates the relationship between employability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
(100 reference statements)
0
5
0
1
Order By: Relevance
“…Finally, the mechanism between decent work and career exploration behaviors is not clearly identified. Future studies should introduce some variables, such as employability [74], to further explore the relationship between the two.…”
Section: Contributions Implications and Future Research Directionsmentioning
confidence: 99%
“…Finally, the mechanism between decent work and career exploration behaviors is not clearly identified. Future studies should introduce some variables, such as employability [74], to further explore the relationship between the two.…”
Section: Contributions Implications and Future Research Directionsmentioning
confidence: 99%
“…Previous research showed that employers are more likely to invest in developing employee competencies when they maintain a long-term relationship with the company (Peng et al. , 2019).…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…Previous studies have shown that employers invest less in developing competencies of the employees working based on unstable FoEs (e.g. Bernstrøm et al, 2019;Peng et al, 2019;Poulissen et al, 2023), though the problem of shaping future competencies has not yet been addressed. Furthermore, previous research primarily focused on identifying the differences between people working under employment contracts and self-employed people (Baluku et al, 2020;Gish et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Some have argued that training, which could improve employability (Snydrova et al, 2020), would promote increased job satisfaction (Popescu & Roman, 2018). Job satisfaction has been linked to enhanced organizational commitment that would address the problem of turnover (González‐Romá et al, 2016; Peng et al, 2019). However, other researchers have demonstrated that employees were more likely to leave an organization after having received training if their salaries were not increased (Leider et al, 2021).…”
Section: Introductionmentioning
confidence: 99%